The effectiveness of sensory stimulation therapy to strengthen the resilience of operating room nurses - Chantal Marais; Emmerentia Du Plessis; Magdalene P Koen (AOSIS, 2016)
Background: Operating room (OR) nurses need to be resilient in order to cope with extreme demands in their workplace. This research focused on the effectiveness of sensory stimulation therapy (SST) to strengthen the resilience of nurses in the OR of a private hospital in the North West Province. Purpose: The purpose was to determine the effectiveness of SST as an intervention to strengthen the resilience of OR nurses.Design: A quasi-experimental design was used. Method: The population consisted of OR nurses and ICU nurses at private hospitals in the North West Province. All-inclusive sampling was used. Forty-one OR nurses formed the intervention group. A pilot group (8 subjects, OR nurses), as well as a comparison group (23 subjects, ICU nurses), was also sampled. An intervention, namely SST, was implemented with the intervention group. The resilience of the intervention group, pilot group and comparison group was measured before and after the implementation of the SST by means of Wagnild and Young's resilience questionnaire. The intervention group also completed a self-report questionnaire on their needs and suggestions for SST and wrote short narratives on their experience of SST. Data were analysed using descriptive and inferential statistics, and by thematic coding. Results: Results indicated a significant statistical increase in the intervention group's resilience levels. Results from the narratives confirmed that the intervention group's resilience may have been strengthened through SST. Conclusion: SST has potential to strengthen the resilience of OR nurses.